THE ROLE OF WOMEN IN FOOD PRODUCTION AND POVERTY REDUCTION IN RURAL COMMUNITIES IN CROSS RIVER STATE - Otu, Judith; Anam, Bassey (Advances in Social Sciences Research Journal, 2016)
Women play significant roles in the development of the rural economy. The study examines their role in food production and poverty reduction in rural communities in Cross River State. The research design adopted for the study was survey research design. The population comprised of Agricultural extension workers and rural farmers in the southern senatorial district of Cross River State. The local government areas used in the study included, Akpabuyo, Bakassi, Calabar Municipality, Calabar South, Akamkpa and Odukpani. A sample population of 360 was systematically drawn from the sample area. Data obtained was analyzed using Mean and standard deviations. The result obtained showed that access to land, capital, and equipments significantly impacts on the level of food production and poverty reduction by rural women. Also, access to primary health care services significantly impacts on the level of food production and poverty reduction by rural women. Based on this conclusion, the study recommends the need to improve access to land and other economic resources so as to enhance the productive capacity of rural women.